Serum and glucocorticoid-regulated kinase 1: Structure, biological functions, and its inhibitors - Jang, Hyunsoo; Park, Youngjun; Jang, Jaebong (Frontiers in Pharmacology, 2022)
Serum and glucocorticoid-regulated kinase 1 (SGK1) is a serine/threonine kinase belonging to the protein kinase A, G, and C (AGC) family. Upon initiation of the phosphoinositide 3-kinase (PI3K) signaling pathway, mammalian target of rapamycin complex 2 (mTORC2) and phosphoinositide-dependent protein kinase 1 (PDK1) phosphorylate the hydrophobic motif and kinase domain of SGK1, respectively, inducing SGK1 activation. SGK1 modulates essential cellular processes such as proliferation, survival, and apoptosis. Hence, dysregulated SGK1 expression can result in multiple diseases, including hypertension, cancer, autoimmunity, and neurodegenerative disorders. This review provides a current understanding of SGK1, particularly in sodium transport, cancer progression, and autoimmunity. In addition, we summarize the developmental status of SGK1 inhibitors, their structures, and respective potencies evaluated in pre-clinical experimental settings. Collectively, this review highlights the significance of SGK1 and proposes SGK1 inhibitors as potential drugs for treatment of clinically relevant diseases.